CD38‐Targeted Theranostics of Lymphoma with 89Zr/177Lu‐Labeled Daratumumab. Issue 10 (15th March 2021) - Kang, Lei; Li, Cuicui; Rosenkrans, Zachary T.; Huo, Nan; Chen, Zhao; Ehlerding, Emily B.; Huo, Yan; Ferreira, Carolina A.; Barnhart, Todd E.; Engle, Jonathan W.; Wang, Rongfu; Jiang, Dawei; et al.
Abstract: Lymphoma is a heterogeneous disease with varying clinical manifestations and outcomes. Many subtypes of lymphoma, such as Burkitt′s lymphoma and diffuse large B cell lymphoma, are highly aggressive with dismal prognosis even after conventional chemotherapy and radiotherapy. As such, exploring specific biomarkers for lymphoma is of high clinical significance. Herein, a potential marker, CD38, is investigated for differentiating lymphoma. A CD38‐targeting monoclonal antibody (mAb, daratumumab) is then radiolabeled with Zr‐89 and Lu‐177 for theranostic applications. As the diagnostic component, the Zr‐89‐labeled mAb is highly specific in delineating CD38‐positive lymphoma via positron emission tomography (PET) imaging, while the Lu‐177‐labeled mAb serves well as the therapeutic component to suppress tumor growth after a one‐time administration. These results strongly suggest that CD38 is a lymphoma‐specific marker and prove that 89 Zr/ 177 Lu‐labeled daratumumab facilitates immunoPET imaging and radioimmunotherapy of lymphoma in preclinical models. Further clinical evaluation and translation of this CD38‐targeted theranostics may be of significant help in lymphoma patient stratification and management. Abstract : A CD38‐targeting monoclonal antibody (mAb, daratumumab) is radiolabeled with Zr‐89 and Lu‐177 for theranostics. As the diagnostic component, the Zr‐89‐labeled mAb is highly specific in delineating CD38‐positive lymphoma via positron emission tomography imaging, while the Lu‐177‐labeled mAb serves well as the therapeutic component to suppress tumor after a one‐time administration. Further clinical translation may be of high significance for lymphoma.